Satellite tracking reveals a new migration route of black-necked cranes (Grus nigricollis) in Qinghai-Tibet Plateau - Ye Wang; Chunrong Mi; Yumin Guo (PeerJ, 2020)
Background The black-necked crane (Grus nigricollis) is a vulnerable species and the only species that lives in the plateau. Five migration routes of different populations have been identified, but for cranes wintering in Nyingchi Prefecture, Tibet, the migration route and breeding/summering area are still unknown. The aim of this study was to investigate the spatio-temporal migration patterns of black-necked cranes in this area and to identify important areas for conservation. Methods In 2016, we fitted seven black-necked cranes in Nyingchi with GPS-GSM satellite transmitters to record their migration routes. We used ArcGIS 10.2 to visualize important stopover sites and the ‘ggplot’ function in R to analyze the migration patterns. Results From March 2016 to May 2019, we recorded nine spring migration and four autumn migration tracks from five individuals. Four individuals spent the breeding/summering season in Qinghai Lake, while the other spent the breeding/summering season in the Jinzihai Wetland of Dulan County, Qinghai Province. Detailed spatio-temporal information showed that the spring migration lasted 8.7 ± 4.6 days and covered 1,182.5 ± 90.4 km, while the autumn migration lasted 30 ± 10.6 days and covered 1,455.7 ± 138 km. Basom Lake and the Shazhuyu River were the most important stopover sites during the spring and autumn migrations, respectively. The cranes spent 4.4 ± 3.7 days in Basom Lake and 26.3 ± 10.7 days in the Shazhuyu River. The black-necked cranes mainly migrated during the daytime (>85 % of the fly points), and 81 % (17/21) of all stopover and roosting sites were in the valley or at lakeside swamps. Only 17.7% (516 / 2,914) of the data points for stopover and roosting sites were in protected areas. Main conclusions Our study revealed the breeding/summering areas and migration routes of the black-necked cranes wintering in Nyingchi. These results contribute to a better understanding of the annual spatio-temporal migration patterns and the development of conservation plans for this vulnerable species.